Impacts of climate change on biodiversity and ecosystems in Bavaria: a sectoral analysis - Sven Rubanschi; Anne Lewerentz; Andreas Krause; Jana Blechschmidt; Stefan Fallert; Elizabeth Gosling; Konstantin Gregor; Isabelle Jarisch; Christian Stetter; Maximilian Brönner; Florian Hartig; Markus Hoffmann; et al. (Regional Environmental Change, 2026)
Climate change is expected to create a range of impacts on biodiversity, land use, and economic activities, but those sector impacts are rarely analysed together. Here, we assess how climate change and socioeconomic narratives will affect land use and biodiversity in the state of Bavaria, Germany. We apply a multi-sectoral modelling approach with two climate projections (RCP 2.6 and 8.5) downscaled from three different climate models in combination with three land-use scenarios: biodiversity protection, climate change mitigation, and climate change adaptation. We evaluate changes in different sectors such as forestry and agriculture, considering impacts on carbon storage, terrestrial and aquatic biodiversity, and the adaptation of agricultural practices. In our simulations, biodiversity declined sharply under the higher emission scenario, highlighting climate change as a major threat to biodiversity in Bavaria. Prioritising biodiversity through forest conversion and expanding pasture reduced species decline and enhanced carbon storage more effectively than pure climate-focused mitigation. Climate change intensity had minimal impacts on land-use patterns (e.g. allocation of forest types), but it significantly changed farmers’ preferences, increasing their inclination toward more conservative land management practices, i.e. favouring the status quo. We conclude from our findings that policymakers should strategically prioritise biodiversity protection alongside targeted forest-management practices to simultaneously enhance ecosystem health, biodiversity, and carbon storage. Intensified agricultural and land management, on the other hand, should be approached cautiously to avoid biodiversity loss.